1982
DOI: 10.1016/s0140-6736(82)90809-1
|View full text |Cite
|
Sign up to set email alerts
|

Oral Contraceptives and Rheumatoid Arthritis: Further Evidence for a Preventive Effect

Abstract: CD, Stewart CT, Hamilton A, Salmon RJ. Infection as a cause of folic acid deficiency and megaloblastic anaemia. Am J Dis Child 1952; 84: 718-28. 12 Panders J, Rupert S. The effect oftemperature on folic acid metabolism. Br J Haematol 1965; 11: 518-24. 13 Jennette J, Goldman I. Inhibition of the membrane transport of folate by anions retained in uraemia. J Lab Clin Med 1975; 86: 834-43

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0

Year Published

1985
1985
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(48 citation statements)
references
References 8 publications
(1 reference statement)
0
48
0
Order By: Relevance
“…When compared with women who never used oral contraceptives, women who were ever users had a relative risk of RA of 1 .O (95% confidence interval [CI] 0.7-1.3), those who were current users had a relative risk of 0.6 (95% CI 0.1-2.6), and those who were past users had a relative risk of 1.0 (95% CI 0.7-1. 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When compared with women who never used oral contraceptives, women who were ever users had a relative risk of RA of 1 .O (95% confidence interval [CI] 0.7-1.3), those who were current users had a relative risk of 0.6 (95% CI 0.1-2.6), and those who were past users had a relative risk of 1.0 (95% CI 0.7-1. 3).…”
Section: Resultsmentioning
confidence: 99%
“…The Royal College of General Practitioners' Oral Contraceptive Study (2) yielded the first report of a reduction in the incidence of RA among current users of oral contraceptives; a 2-fold reduction was found. Vandenbroucke et al (3) reported that women who were current or past users of oral contraceptives had a 50% lower risk of RA compared with women who had never used oral contraceptives. However, Linos et a1 (4) observed no evidence of a protective effect, in a study of residents of Olmsted County, Minnesota.…”
mentioning
confidence: 99%
“…The increased female susceptibility to rheumatoid arthritis, in contrast, is probably not mediated b y female sex hormones (31). In fact, it has been reported that contraceptive treatment ameloriates rheumatic symptoms (32,33). Thus, an intriguing possibility is that the basic mechanism b y which sex hormones influence the expression of autoimmunity is shared between rheumatoid arthritis in humans and collagen-induced arthritis in mice.…”
Section: Discussionmentioning
confidence: 98%
“…[42][43][44][45][46] The majority of studies have found that past or current use of COCs has a protective effect against RA development. 47 In a recent case-control study, Berglin et al 48 reported a decreased risk for development of RA in women who had been using COCs for 7 years or more (OR: 0.37; 95% CI: 0.15-0.93).…”
Section: Rheumatoid Arthritismentioning
confidence: 99%